2002
DOI: 10.1002/da.10024
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of late-onset OCD following basal ganglia infarct

Abstract: Current consensus on the treatment of obsessive-compulsive disorder (OCD) includes cognitive behavior therapy (CBT) in the form of exposure and response prevention (ERP). However, the generalizability of these methods to elderly populations remains largely undocumented. This clinical case study examines the effectiveness of medications and intensive, inpatient ERP in an elderly patient with onset of OCD following basal ganglia infarcts. There was a dramatic reduction from baseline to follow-up in both obsessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 15 publications
1
37
0
2
Order By: Relevance
“…The second hypothesis is based on the existence of a pathophysiological substrate related to the basal ganglia described in functional imaging studies for both BS 1 and OCD 25,26 , supporting the classical interpretation of this co-existence as secondary to behavioral related cortico-striatal circuitry dysfunction. Reinforcing this hypothesis, obsessive-compulsive symptoms have been described after focal lesions involving the basal ganglia 27 , besides being part of the clinical expression of disorders classically related to pathological abnormalities of this brain region such as post-encephalitic parkinsonism, Gilles de la Tourette syndrome and pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection; Sydenham chorea and hereditary myoclonus-dyston i a 2 0 , 2 8 -3 0…”
Section: Discussionmentioning
confidence: 95%
“…The second hypothesis is based on the existence of a pathophysiological substrate related to the basal ganglia described in functional imaging studies for both BS 1 and OCD 25,26 , supporting the classical interpretation of this co-existence as secondary to behavioral related cortico-striatal circuitry dysfunction. Reinforcing this hypothesis, obsessive-compulsive symptoms have been described after focal lesions involving the basal ganglia 27 , besides being part of the clinical expression of disorders classically related to pathological abnormalities of this brain region such as post-encephalitic parkinsonism, Gilles de la Tourette syndrome and pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection; Sydenham chorea and hereditary myoclonus-dyston i a 2 0 , 2 8 -3 0…”
Section: Discussionmentioning
confidence: 95%
“…However, other findings suggest a possible role also for dopamine and dopamine receptors. In particular, (a) dopamine regulates cortico-striatal-thalamo-cortical circuits through its activity on indirect and direct pathway (Alexander and Crutcher, 1990); (b) structural damages to the basal ganglia, a region particularly rich in dopamine receptors, promote OCD symptoms (Carmin et al, 2002); (c) a supersensitivity to cataleptic induction by the D 2 receptor antagonist sulpiride was observed in the D1CT mice, an animal model that shows symptoms of human compulsive disorders associated with cortical-limbic hyperactivity (Campbell et al, 1999); (d) differences in D 2 dopamine receptor binding in the head of the caudate nucleus predict phenotypic severity in monozygotic twins discordant for Tourette syndrome severity (Wolf et al, 1996); and (e) a reduced availability of D 2 receptors subtypes has been recently described in the left caudate nucleus of patients with OCD (Denys et al, 2004). In addition, preclinical studies on rodents indicated that the repeated administration of antidepressants affect dopamine D 2 receptors (Ainsworth et al, 1998a;Ainsworth et al, 1998b;Spyraki and Fibiger, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have indicated that the majority of these patients had a relatively poor outcome, with limited response to psychotropic medication (Weiss and Jenike 2000); others have concluded that the presumed organic aetiology in late-onset OCD does not preclude the possibility of successful treatment (Philpot and Banerjee 1998;Carmin et al 2002). In this patient, however, the unusual response to SSRIs and the eventual poor outcome was in all probability related to the underlying condition, i.e.…”
Section: Discussionmentioning
confidence: 82%